Handbook of the economics of giving, altruism and reciprocity - Kolm, Serge-Christophe.; Mercier Ythier, J. (Jean) (Amsterdam ; London : Elsevier, 2006)
The Handbook of the Economics of Giving, Altruism and Reciprocity aims to provide a definitive source, reference guide, and teaching supplements for its field. It surveys, as of the early 2000's, the state of the art of the economic theory and of the econometric and statistical study of its objective, and it also provides extensive reviews of the contemporary contributions of the other discipline concerned by domain, such as anthropology, psychology, philosophy, political science, sociology, biology and socio-biology. In addition to its use as a reference guide, the Editors hope that this Handbook will assist researchers and students working in a particular branch of this vast field to become acquainted with other branches. Each of the chapters can be read independently.
v. 1. Foundations -- v. 2. Applications.
Includes bibliographical references and indexes.
rpm 12/11/13
Loans
Keywords: Distributive justice; Economics -- Sociological aspects; Charity; Altruism; Voluntarism; Gifts; Economic assistance